Heparan sulfate proteoglycan-dependent neutrophil chemotaxis toward PR-39 cathelicidin - Patsch Josef R; Ricevuti Giovanni; Ross Christopher R; Kaneider Nicole C; Mosheimer Birgit; Djanani Angela; Wiedermann Christian J (BMC, 2006)
Abstract Cathelicidins are mammalian proteins containing a C-terminal cationic antimicrobial domain. Porcine PR-39 cathelicidin affects leukocyte biology. Mechanisms of action may involve alteration of heparan sulfate proteoglycan-dependent functions in inflammatory cells. It was tested whether PR-39 affects human neutrophil migration and if such effects involve heparan sulphate proteoglycans. Neutrophils were from forearm venous blood of healthy donors. Migration was tested in modified Boyden chamber assays. Involvement of heparan sulfate proteoglycans was tested by their chemical modification and by the use of specific antibodies. PR-39 induced migration in neutrophils in a concentration dependent manner. Modification of heparan sulfate proteoglycans with sodium chlorate inhibited migration whereas chemotaxis toward the chemoattractant formyl-Met-Leu-Phe was not affected. Removal of heparan sulfates or chondroitin sulfates from the surface of neutrophils by heparinase or chondroitinase inhibited migration toward PR-39. In conclusion, antimicrobial PR-39 stimulates human neutrophil chemotaxis in a heparan sulfate proteoglycan-dependent manner. Involvment of syndecans is likely as both heparinase and chondroitinase were abrogating. Data suggest active participation of heparan sulfate proteoglycans of neutrophils in cathelicidin peptide-mediated regulation of the antimicrobial host defense.